Managing Facilities for Results : Optimizing Space for Services. - Bryan, Cheryl (PLA results series., 2007)
With examples ranging from small to large small public libraries, this volume is equally valuable for school, special, and academic librarians who are faced with similar space repurposing challenges. Any library can embrace these practical, proven techniques for addressing community needs -- by creating a blueprint that prioritizes services and creates the space for them within their existing facility.